Ação tripanocida de um mastoparano de Polybia paulista e seu possível mecanismo de ação - Vinhote, Juliana Freire Chagas (2015)
Chagas disease, a neglect ed disease, is a parasitic infection caused by Trypanosoma cruzi (T. cruzi) and is endemic in several countries. In Brazil, only benznidazole is used for treating the disease. In this context, the therapeutic potential of toxins is increasingly gaining gro und and stirring interest in the scientific community. The poisons of invertebrates have become intriguing as a source of bioactive substance. The mastoparan, the most widely described class of peptides isolated from the venom of wasps, already shows diffe rent biological activities. Thus, isolated peptides have attracted scientific interest as a source of molecular model for the possible development of new drug therapies. This study investigated the effect of mastoparan peptide (MP) isolated from the venom of a Polybia paulista wasp on the Y strain of T. cruzi and its possible mechanism of action. Epimastigote forms of T. cruzi were grown, treated with various concentrations of MP, and incubated for 24, 48, and 72 hours. Trypomastigote forms of T. cruzi obta ined by LLCMK2 cells infected were subcultured, treated with various concentrations of MP, and incubated for 24 hours. To investigate the involvement of reactive oxygen species (ROS) in the mastoparan cytotoxic effect on T. cruzi epimastigotes, plates were incubated with IC50 of 24 MP; an analysis of fluorescence emission was performed via flow cytometry after adding dichlorofluorescein (DCF). The mastoparan effect on the mitochondrial membrane potential of epimastigotes was tested with rhodamine 123. Cytot oxicity was assessed on RAW 264.7 cells, and the viability of macrophages was determined using the microculture tetrazolium (MTT) assay. In the study of molecular docking, the three dimensional structure of the mastoparan was originally obtained from the p rimary sequence specific program. After analyzing the binding sites of the peptide and T. cruzi glyceraldehyde 3 - phosphate dehydrogenase (TcGAPDH) enzyme, the crystal structure of the TcGAPDH - chalepina complex was used for comparison. The mastoparan inhibi ted the growth of T. cruzi epimastigotes, with an IC50 of 102 μg/ml, 53.95 μg/ml, and 58.51 μg/ml for 24, 48, and 72 hours of incubation, respectively. In the analysis of the ROS generation, there was a significant increase in the relative fluorescence int ensity compared to the control group. The peptide change had the potential of mitochondrial membrane of the parasite. For trypomastigotes, the IC50 was 8.83 μg/ml after 24 hours of incubation. The cytotoxicity of mastoparan evaluated in macrophages did not induce significant cell death in the different concentrations studied. In the docking study, coupling mastoparan was evidenced in TcGAPDH, showing different binding sites residue of the enzyme's active center amino acids and comparing the similar position occupied by the molecule in TcGAPDH - chalepina. It follows that the mastoparan showed trypanocidal activity involving the involvement of oxidative stress and changes in membrane potential without displaying cytotoxic cells; the macrophages seem to inhibit TcGAPDH T. cruzi. Therefore, the mastoparan stands out as an important bioactive molecule against parasites.